Enhancement of SUV Roll Dynamics using Fuzzy Logic Control - Phuman Singh, A.S. (2011)
This paper presents the development of roll control using feedforward fuzzy control for improvement of vehicle roll dynamics. The mathematical equations of the full car vehicle model were derived and the Matlab/SIMULINK model was developed. The tire model integrated to the vehicle model was represented using loop up table method. The parameters of sport utility vehicle were used for simulation purpose. The vehicle model was validated using CarSim software for double lane change maneuver. From the simulation results, the trend and magnitude of the vehicle model responses were similar to that of CarSim. A roll control strategy using road steering wheel angle and vehicle longitudinal velocity as the inputs fuzzy control was developed and implemented on the validated vehicle model. The controller performance for Fishhook and step steer maneuvers has proven the capability of the proposed control strategy in reducing the tendency to rollover.